Respuesta :
The missing reason is the following:
8. Substitute [tex]x=\cos A[/tex] is the equation of statement 5:
[tex]a^2=b^2-2bcx+c^2[/tex]
8. Substitute [tex]x=\cos A[/tex] is the equation of statement 5:
[tex]a^2=b^2-2bcx+c^2[/tex]
Solution: The missing reason in Step 8 is substitution of [tex]x=c\cos (A)[/tex].
Explanation:
The given steps are used to prove the formula for law of cosines.
From step 5 it is noticed that our equation is
[tex]a^2=b^2-2bx+c^2[/tex] ..... (1)
From step 7 it is noticed that the value of [tex]x[/tex] is [tex]c\cos (A)[/tex].
So by substituting [tex]c\cos (A)[/tex] for [tex]x[/tex] in equation (1) we get the equation of step 8, i.e.,
[tex]a^2=b^2-2bc\cos (A)+c^2[/tex]
Hence, the missing reason in Step 8 is substitution of [tex]x=c\cos (A)[/tex].